IOT Based Smart Irrigation System Using Arduino - Rao, J Venkateswara (International Journal of Membrane Science and Technology, 2023)
Agriculture is a crucial part of many national economies, but traditional irrigation techniques often fall short in terms of water efficiency and control. To address these limitations, this project presents an IoT-driven smart irrigation system. The system utilizes a network of sensors and actuators to continuously monitor factors like soil moisture, temperature, humidity, and weather conditions. This data is analyzed by a central control unit, which applies algorithms to determine the most efficient irrigation schedules and water usage. Designed to be both energy-efficient and cost-effective, the system operates using a standard power source. This smart irrigation system offers several advantages over conventional methods, including reducing water wastage and conserving resources, which ultimately leads to increased crop yields and cost savings. The system is also user-friendly, simple to install, and easy to maintain, with customization options for various crops and soil types. Furthermore, its scalability allows it to be extended to larger areas or multiple fields. In summary, this IoT-based irrigation solution represents a significant advancement over traditional systems, providing modern agriculture with a sustainable, efficient, and flexible tool. Its energy efficiency, scalability, and adaptability make it an ideal option for farmers seeking to improve their irrigation practices through innovative technology.